Promotion of Human Capital in Traditional Fishing Villages: An Empirical Analysis - Rashid, Mohammed Mamun; Singh Jamir Singh, Paramjit; Azman, Azlinda (Journal of Emerging Markets and Management, 2025)
Bangladesh is a lower-categorized middle-income country where traditional fishermen, here, Jaladas are at extreme risk of long-lasting poverty. Two Jaladas villages were study locations where an endeavor was carried out to identify major driving forces causative for promoting human capital in these communities, and socio-economic transformations through this process. This study adopted a qualitative method, specifically, Focus Group Discussion (FGD). In addition, a 100-household survey was conducted by random sampling. The findings revealed that NGO-led interventions increase awareness, leadership, education, training and skill development, and access to health facilities. The quality of lives and livelihoods has improved through human capital development in one of the villages studied. Human capitals contribute in socio-economic transformation especially, in the areas of employment, income, housing, drinking water, sanitation, fish marketing, self-help groups, social alliances and networking, claiming rights & entitlements, and bargaining power. Another study village was lagging behind due to inadequate attention from the Government of Bangladesh (GoB), private sector, donor-funded NGOs, and other actors. This study critically analyzes the reasons for advancement and lagging behind between the two study villages through a human capital lens. This study urges to bring the disadvantaged Jaladas communities into the mainstreaming and sustainable development process.